2008
DOI: 10.1063/1.2883960
|View full text |Cite
|
Sign up to set email alerts
|

Spreading fronts in sedimentation of dilute suspension of spheres

Abstract: The thickness of the diffuse front between a sedimenting dilute suspension and the clear fluid above grows linearly in time due to polydispersity in the size of the particles and due to a hydrodynamic effect in which randomly heavy clusters fall out of the front leaving it depleted. Experiments and simplified point-particle numerical simulations agree that these two effects are not simply linearly additive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…This relationship is found to capture the behavior of our experimental materials in a simplified 2D Hele-Shaw geometry in the limit of dilute suspension (5 × 10 −4 < C < 5 × 10 −2 ) such as a = 1.2 with R 2 = 0.953. Moreover, it is fully consistent with previous experimental results on particle sedimentation in dilute suspensions (Bergougnoux et al, 2003;Chehata Gomez et al, 2008, 2009.…”
Section: B Light Attenuation Techniquesupporting
confidence: 81%
See 1 more Smart Citation
“…This relationship is found to capture the behavior of our experimental materials in a simplified 2D Hele-Shaw geometry in the limit of dilute suspension (5 × 10 −4 < C < 5 × 10 −2 ) such as a = 1.2 with R 2 = 0.953. Moreover, it is fully consistent with previous experimental results on particle sedimentation in dilute suspensions (Bergougnoux et al, 2003;Chehata Gomez et al, 2008, 2009.…”
Section: B Light Attenuation Techniquesupporting
confidence: 81%
“…The effect of multiple scattering is considered to be small (within the error bars in Fig. 4 of the paper) at the low concentration used in this study, which is consistent with our 2D experiments and previous published work (Bergougnoux et al, 2003;Chehata Gomez et al, 2008, 2009). …”
Section: B Light Attenuation Techniquesupporting
confidence: 81%
“…In the Newtonian case [ Fig. 4(a)], a diffuse concentration front is found to develop and spread at the interface with the clear fluid, as previously characterized in experiments and simulations; 8,12,48 however, the concentration profile remains nearly uniform and equal to the mean concentration in the bulk of the suspension away from the front, except in the late stages of the sedimentation process when the front becomes very broad. In a viscoelastic fluid [Figs.…”
Section: B Results and Discussionmentioning
confidence: 58%
“…While this differs from the no-slip boundary condition applying at the walls of a rigid container, it has the advantage of allowing for a very efficient spectral solution while preventing fluid penetration at the boundaries, a feature that has previously been shown to be critical in sedimentation simulations. 7 Previous simulations of sphere suspensions, 8,12,48 as well as spheroid suspensions, 32,33 have demonstrated that this boundary condition is sufficient to capture most salient features observed in sedimentation experiments, including the decay of velocity fluctuations in sphere suspensions, 12 and a wavenumber selection for density fluctuations in spheroid suspensions. 33 Note, however, that owing to the freeshear-stress condition there is no resistance to tangential flow close the the boundaries, which may have a quantitative effect on velocity fluctuations in the suspensions.…”
Section: Mean-field Flow Solutionmentioning
confidence: 95%
“…Polydispersity in the particle size, and Brownian motion of colloidal sized particles, may cause the thickness of this interface to increase in time. 7 Sedimentation continues until all of the dispersed phase is contained within the sediment bed, with only clear fluid above. When this is the case, complete phase separation has occurred.…”
Section: Introductionmentioning
confidence: 99%